The Influence of Public Consciousness on Spriritual Revival and Development of Kazakhstan (Journal of Philosophy Culture and Political Science, 2019)
The paper studies the problem of modernization of public consciousness and the revival of spiritual and moral values in Kazakhstan. The study is based on the analysis of a wide range of developmental theories, including civilizational, Eurasian, sociocultural theories, modernization theory, etc. These concepts, however, according to the authors, do not reveal in full the influence of advanced development of public consciousness on modernization process. The authors conclude that Kazakhstan will be successfull in overcoming its cultural, economic, social, and political challenges precisely on the basis of consolidation of values such as the new Kazakhstani patriotism, unity of the people, respect for the country’s historical roots and traditions, innovation culture along with continuous adjustment to global realities. The nationwide program for Kazakhstan’s spiritual revival«Roukhani Zangyru» is a successful example of planning the development «with a clearly articulated end goal». The changes in ethical realm prepare and legitimize the changes of political and economic institutions of Kazakhstan’s society, as well as the formation of new social institutions.The study presented in this paper can have ist practical implementation as a new special course «Modernization of the public consciousness of Kazakhstani society».Key words: development, culture, modernization, society, consciousness, spiritual revival.